2018 Kansas Summer Annual Forage Hay and Silage Variety Trial - J. D. Holman; A. Obour; A. Esser; Jane Lingenfelser; T. Roberts; S. Maxwell (Kansas Agricultural Experiment Station Research Reports, 2019)
In 2018, summer annual forage variety trials were conducted across Kansas near Garden City, Hays, and Scandia. All sites evaluated hay and silage entries. Companies were able to enter varieties into any possible combinations of research sites, so not all sites had all varieties. Across the sites, a total of 77 hay varieties and 87 silage varieties were evaluated.
Keywords: Forage